Pematahan Dormansi Benih Merbau (Intsia bijuga (Colebr.) O. Kuntze) dengan Perlakuan Lama Perendaman dalam Air Kelapa - Maria Rosalina Bunga Leutuan; Mamie E. Pellondo’u; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Merbau (Intsiabijuga(Colebr.) O. Kuntze) is a native plant species in Indonesia and widely used by local people because it has high economic values. The generative propagationof Merbau had problems due to the period of seed dormancy, so pretreatment was required to defeat this dormancy. Coconut water one the natural ingredients, which contains cytokinin, auxin and gibberellins and other compounds that can stimulate seed germination and growth of Merbau. Soaking the seeds in coconut water is a way to break the dormancy of physical seed of Merbau, expectedto accelerate germination and reducing time and effort forbreaking merbau seed dormancy. This study aimed to the effect ofsoaking coconut water on Merbau seeds in different immersion time the best seedlings growth of Merbau. This study used a completely randomized design (CRD) with a long soaking time (A0) merbau seeds soaked in water for 24 hours (control), (A1) merbau seeds soaked 500 mL pure coconut water for 24 hours, (A2) merbau seeds soaked 500 mL pure coconut water for 48 hours, (A3) merbau seeds soaked in 500 mL pure coconut water for 72 hours. This study found the length of immersion time had a very significant effect to the percentage germination and vigor index but had nosignificant effect on the germination rate. Single factor (A3) merbau seeds soaked 500 mL pure coconut water for 72 hours the best treatment because it has been able to show a high influence on several observation variables.